Food Grade Oil Quality of Peanut (Arachis hypogaea L.) - BİLMEZ ÖZÇINAR, Aynur and BİLMEZ ÖZÇINAR, Aynur (MAS Journal of Applied Sciences, 2022)
High-oil crop peanut has about 50% edible oil content. Major components of fatty acids of peanutoil are unsaturated fatty acids (oleic acid and linoleic acid). Oxidative stability is an important factor inpeanut process industry. High-oleic peanut contains ≥72% oleate and <8% linoleate and preferred by oilprocessors and consumers. High-oleic peanuts provide a spectrum of nutrients and have improved sensoryproperties and technological advances beyond conventional peanuts. Also relation of enviromental stressfactors with quality are mentioned here below in this review.